An Insight Into Maternal Death Caused by Postpartum Hemorrhage in Western Timor, Indonesia - Kristiani Desimina Tauho; Ferry Fredy Karwur (Jurnal Keperawatan Indonesia, 2019)
Maternal deaths in Timor Island, East Nusa Tenggara Province, are one of the contributors to the overall maternal mortality rate (MMR) of Indonesia. The MMR of Western Timor Island was 150/100,000 live births in 2015. The aim of this qualitative study was to explore the perceived causes of maternal death due to postpartum hemorrhage. Data were obtained from family members, traditional birth attendants, and Posyandu cadres, as well as health providers. Using the retrospective method, this study traced six out of nine postpartum hemorrhage cases in the four sub-districts with the highest maternal death rate in 2010. The research findings showed that most childbirth processes were done at home without any help from health workers. Postpartum hemorrhage happened among women ranging from 24-42 years old; five among them had been pregnant more than four times. Medically, five cases were caused by a prolonged third stage of labor due to a retained placenta. Non-medical factors causing postpartum hemorrhage were poor accessibility, lack of communication devices, and lack of infrastructure.  Keywords: maternal death, postpartum hemorrhage, Western Timor Abstrak Pengetahuan Tentang Kematian Maternal Karena Perdarahan Postpartum di Timor Barat, Indonesia. Kematian maternal di Pulau Timor, Provinsi Nusa Tenggara Timur, merupakan salah satu penyumbang Angka Kematian Ibu (AKI) di Indonesia. Tahun 2015, AKI di Pulau Timor bagian barat adalah sebesar 150/100.000 kelahiran hidup. Tujuan dari studi kualitatif ini adalah untuk mengeksplorasi persepsi para pihak yang paling mengetahui mengenai penyebab kematian maternal karena perdarahan postpartum. Data diberikan oleh anggota keluarga, dukun bersalin, dan kader Posyandu, serta penyedia layanan. Menggunakan metode retrospektif, penelitian ini menyusur enam dari sembilan kasus perdarahan postpartum yang terjadi di empat kecamatan yang memiliki angka kematian maternal tertinggi pada tahun 2010. Hasil penelitian menunjukkan bahwa sebagian besar prosedur persalinan dilakukan di rumah tanpa bantuan dari tenaga kesehatan. Perdarahan postpartum terjadi di antara wanita dengan rentang umur 24–42 tahun; empat di antara mereka sudah pernah hamil sebanyak lebih dari empat kali. Secara medis, lima kasus disebabkan oleh perpanjangan kala tiga persalinan berhubungan dengan retensi plasenta. Faktor- faktor non medis yang menyebabkan perdarahan posrpartum adalah aksesibilitas yang buruk, ketiadaan piranti komunikasi, dan kurangnya infrastruktur. Kata kunci: kematian ibu, perdarahan postpartum, Timor Barat